John Covode papers - Covode, John, 1808-1871.
Incoming correspondence together with a draft of a report by Covode on conditions in the Mississippi Valley after the Civil War. Correspondents include Thomas E. Cochrane, Andrew Gregg Curtin, Alexander K. McClure, Edwin McMasters Stanton, Gideon Welles, and Henry White. Covode's report is printed in the Report of the Joint Committee on Reconstruction (1866), part 4, page 114.
U.S. representative from Pennsylvania.
Collection material in English.
Keywords: Cochrane, Thomas E. -- Correspondence; Curtin, Andrew Gregg, -- 1817-1894 -- Correspondence; McClure, Alexander K. -- 1828-1909 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869 -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; White, Henry, -- Pennsylvania legislator -- Correspondence; United States. -- Congress. -- Joint Committee on Reconstruction; Reconstruction (U.S. history, 1865-1877); Mississippi River Valley -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Representatives, U.S. Congress -- Pennsylvania